Comparative evaluation of silver diamine fluoride, glass ionomer cement, and calcium hydroxide for indirect pulp therapy in young permanent molars: A randomized controlled trial - Tejaswini M Ghorpade; Devendra P Patil; Farhin Alimiya Katge; Vamsi Krishna Chimata; Parin Bhanushali (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Objectives: Comparative evaluation of indirect pulp therapy (IPT) with silver diamine fluoride (SDF), Type VII glass ionomer cement (GIC), and calcium hydroxide (Ca(OH)2) in young permanent molars. Materials and Methods: This was randomized controlled trial, in which 45 children with 60 young permanent first molars were allocated as; Group A: IPT with SDF, Group B: Type VII GIC, and Group C: Ca(OH)2. Clinical and radiographic evaluation and comparison was done at baseline, 3, 6, 12 months. Data analysis was done using Chi-square test, one way ANOVA, Tukey’s post hoc analysis test. The level of significance was set at P < 0.05. Results: On statistical analysis IPT with SDF showed 88.2%, Type VII GIC showed 94.1% and Ca(OH) 2 showed 88.2% success at 12 months’ follow-up. However, intergroup comparison showed no statistical significant difference. The mean dentin bridge formation in SDF was 0.5467 ± 0.08338 mm, Type VII GIC (0.4813 ± 0.06551 mm) and Ca(OH)2 group (0.5 ± 0.07559 mm), which was statistically significant with a P = 0.049. Conclusions: On comparative evaluation, clinical and radiographic success for IPT with SDF, Type VII GIC and Ca (OH) 2 were comparable. This study also concluded SDF and Type VII GIC can be used as IPT agents in permanent teeth. Dentin bridge formation was more in SDF followed by Ca(OH)2 and Type VII GIC, respectively.